MENUNDA BERSUCI SEHABIS HAIDH DI KALANGAN MAHASISWI FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN ANTASARI - Mashunah Hanafi (Syariah: Jurnal Hukum dan Pemikiran, 2015)
Haidh is an unique cases for women and usually it has a cycles. How if we postpone to purified when haidh has done. This paper will discuss about the reason of women students college who postpone their time to purified, and explore the Islamic view to responds this problem. This research find that the most of reasons of delay are: first, to make sure that their haidh are not exist anymore, and second, because they want to go to college. Based Islamic views, the reason to make sure whether haidhs blood completly stoped is permitted, but no more than one day. But, if the reason is to go to college, it is forbidden because it was included as negligence of shariah.